Ir-REDD-ucible: Addressing the Policy Persistence of Nature-Based Offsetting - Rizzi, Andrea (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2025)
Despite a flurry of critical scholarship and bad press on reputable media outlets, nature-based ‘solutions’ to the climate crisis do not appear to be losing credibility within climate mitigation agendas. In fact, carbon markets are still growing, with carbon forestry as one of their most substantial drivers. While a disconnect between academia and policy comes as no surprise, a close look at almost two decades of academic and grey literature reveals several flaws and helps to explain why critical takes on carbon offsetting may have failed to make a dent in the carbon trading paradigm. Informed by insights from geography, political ecology, and critical development studies, this paper aims to tackle these challenges by interrogating the existing literature and proposing a research agenda for more insightful knowledge production and dissemination.